1998
DOI: 10.1159/000024022
|View full text |Cite
|
Sign up to set email alerts
|

Flow–Cytometric Evaluation of Oxidative Burst in Phagocytic Cells of Children with Cystic Fibrosis

Abstract: Objectives: The objective of this study was to assess the dye 2′,7′–dichlorofluorescein (DCF) assay in screening for alterations in polymorphonuclear cell (PMN) and monocyte (MC) oxidative burst of cystic fibrosis (CF) patients. Study design: 56 CF patients aged between 2 and 20 years were investigated. Purified cells were stimulated with phorbolmyristate acetate (PMA) and zymosan (ZX). A range for DCF fluorescence for PMA– and ZX–stimulated and non–stimulated cells was established based on data from 60 healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 13 publications
2
18
0
Order By: Relevance
“…In fact, Gln supplementation in vitro enhances both phagocytosis and ROS production in isolated neutrophils (34) and, in vivo, suppresses IL-8 production by neutrophils (35). Inasmuch as an increased IL-8 production (33) and oxidative burst alterations (36) have been reported in circulating neutrophils from CF patients, the Gln intracellular depletion found in our study may explain these alterations. However, the exact role of neutrophil Gln depletion in the pathogenesis of CF remains to be elucidated.…”
Section: Discussionsupporting
confidence: 61%
“…In fact, Gln supplementation in vitro enhances both phagocytosis and ROS production in isolated neutrophils (34) and, in vivo, suppresses IL-8 production by neutrophils (35). Inasmuch as an increased IL-8 production (33) and oxidative burst alterations (36) have been reported in circulating neutrophils from CF patients, the Gln intracellular depletion found in our study may explain these alterations. However, the exact role of neutrophil Gln depletion in the pathogenesis of CF remains to be elucidated.…”
Section: Discussionsupporting
confidence: 61%
“…Earlier work has demonstrated a decreased release of reactive oxygen species from CF neutrophils in response to fMLP compared to controls [27]. Studies using PMA and zymosan found that, in some CF patients, oxidative activity was higher than in controls, but in other patients, it was found to be lower than controls, indicating that there was extensive heterogeneity in oxidative activity [29].…”
Section: Discussionmentioning
confidence: 96%
“…Whether failure to kill pathogens results from a primary abnormality of CF neutrophil function, a secondary neutrophil defect related to the CF pulmonary microenvironment, a neutrophil-independent factor, or from a combinatorial effect, is at present unclear. The neutrophil respiratory burst, which results in the generation of potentially injurious oxygen radicals, has been reported to be elevated in cells isolated from CF patients [10]; in other studies the response has been shown to vary according to the infecting pathogen [31] or to the method employed to detect respiratory burst activity [11], and secretory products of Pseudomonas aeruginosa have been reported to suppress neutrophil respiratory burst activity [32]. In this study, we have employed three methods (cytochrome C reduction, lum-DCL and luc-DCL) to quantify the respiratory burst activity of neutrophils isolated (by a method demonstrated to cause minimal disturbance of neutrophil function [24]) from a macrolide-naïve homogeneous patient group (DF508 homozygotes colonised with Pseudomonas aeruginosa) and have demonstrated unequivocally that, in response to soluble ligand stimulation, oxidant output is identical to that from neutrophils from healthy volunteers.…”
Section: Discussionmentioning
confidence: 98%